Audit Committees As Safeguards Against Financial Reporting Risk: Evidence From IFRS 17 Implementation - Fransdito Ali Ilyas; Nijar Kurnia Romdoni; Tedi Rustendi; Dedi Kusmayadi; Desiana (Jurnal Ekonomi Bisnis dan Manajemen, 2026)
This study investigates how audit committee expertise influences financial reporting risk following the implementation of IFRS 17 in Indonesia’s insurance industry. IFRS 17 represents a major regulatory shift emphasizing current fulfillment values and actuarial modeling, which significantly affects earnings volatility. Grounded in agency theory and source credibility theory, the study examines whether financial/industry expertise could mitigate the volatility associated with IFRS 17 adoption. Employing panel data regression on 18 insurance firms listed on the Indonesia Stock Exchange from 2021–2024, the study captures pre- and post-adoption periods. Results reveal that audit committee financial expertise has a significant negative relationship with earnings volatility, indicating its effectiveness in reducing financial reporting risk. Meanwhile, the interaction between financial and industry expertise, though not statistically significant, shows a consistent negative direction, implying potential synergy as expertise matures. Moreover, post-IFRS 17 implementation, earnings volatility decreases modestly, suggesting enhanced reporting stability and transparency. The findings underscore the importance of audit committee competence in navigating complex accounting standards, offering implications for regulators (OJK), insurers, and policymakers to strengthen governance capacity amid regulatory change.